2016
DOI: 10.1016/j.jmbbm.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of contact pressure, cross-shear and counterface material on the wear of PEEK and CFR-PEEK for orthopaedic applications

Abstract: Total joint replacement is a successful surgical intervention for the treatment of the degeneration of many joints, particularly the hip and knee. As the demand for joint replacement grows, and the life expectancy of the population increases, the performance requirements of these implants also changes. New materials, to improve longevity and enhance performance have been explored including PEEK and CFR-PEEK.This study investigated whether CFR-PEEK and PEEK were appropriate materials for total joint replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 30 publications
(66 reference statements)
2
20
0
Order By: Relevance
“…This difference suggests that a hard counter face 225 bearing material directly effects the CS dependency and wear factor of PEEK-OPTIMA 226 bearings. This confirms the effect reported by Brockett et al 21 . There was no significant CS 227 dependency observed for PEEK-OPTIMA pins when articulating on the PEEK-OPTIMA 228 counter face lubricated with a proteinaceous fluid (BCS) in this study, which is a similar 229 characteristic to the results reported by Baykal et al 20 for the all-polymer, PEEK-OPTIMA 230 and polyethylene bearing combinations, and those reported by Laux and Schwartz 31 under dry 231 lubricated conditions, however, at a lower contact pressure of 1.1 MPa.…”
Section: Discussion 210supporting
confidence: 93%
See 2 more Smart Citations
“…This difference suggests that a hard counter face 225 bearing material directly effects the CS dependency and wear factor of PEEK-OPTIMA 226 bearings. This confirms the effect reported by Brockett et al 21 . There was no significant CS 227 dependency observed for PEEK-OPTIMA pins when articulating on the PEEK-OPTIMA 228 counter face lubricated with a proteinaceous fluid (BCS) in this study, which is a similar 229 characteristic to the results reported by Baykal et al 20 for the all-polymer, PEEK-OPTIMA 230 and polyethylene bearing combinations, and those reported by Laux and Schwartz 31 under dry 231 lubricated conditions, however, at a lower contact pressure of 1.1 MPa.…”
Section: Discussion 210supporting
confidence: 93%
“…Brockett et al 21 who found a wear factor of (1.76 ± 2.29) x 10 -6 mm 3 /Nm for PK-on-M under 240 zero CS conditions, with an increase to (7.29 ± 2.18) x 10 -6 mm 3 /Nm when CS was applied. 241…”
Section: Discussion 210mentioning
confidence: 98%
See 1 more Smart Citation
“…Most of the work relating to PEEK composites has been conducted in the lab using standard tribo-meters. For engineering use, some research has been carried out where PEEK composites form the tribological component, including ball bearings [8,24], thrust bearing [25], orthopaedic device [26] and crank shaft bush on the robot joint [27]. There is no work conducted towards journal bearing bushes made of PEEK composites.…”
Section: Introductionmentioning
confidence: 99%
“…This technology is rapidly growing to fabricate patient-specific implants of bone, https://doi.org/10.1016/j.cegh.2019.01.003 Received 4 November 2018; Received in revised form 17 December 2018; Accepted 3 January 2019 prosthetic, heart and its components. 8,9 In medical, the main aim is to maximise the power-to-weight ratio and create development and innovation by using the high-performance material. PEEK is a high-performance polymer which used for manufacturing of medical implants and devices which has a high capability of load bearing.…”
Section: Introductionmentioning
confidence: 99%